Key material for graphene type flame-retardant, light-resistant and wear-resistant waterborne polyurethane coating
By introducing dynamic reverse sulfur bonds, ultraviolet absorbers, nitrogen phosphorus flame retardant, and fragrant beanin derivatives in water -based polyurethane coatings, the polyurethane coatings are prone to yellowing, poor flame retardant, and insufficient wear resistance under ultraviolet rays. The problem realizes higher light resistance, flame retardant and wear resistance.
Patent Information
- Application Number
- CN202411657909.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Water-based polyurethane coatings are prone to yellowing under ultraviolet irradiation, have poor flame retardancy, and insufficient wear resistance, which limits its industrial applications.
A total of dynamic reversal bonds and ultraviolet absorbers are used, combined with nitrogen phosphorus silicon flame retardant and fragrant beanin derivatives, absorb the multiple effects of energy from chemical branches and light to improve the light resistance and flame retardability of polyurethane, and enhance the enhancement Its abrasion resistance.
It significantly improves the yellow -resistant performance, flame retardant performance and wear resistance of polyurethane, extend the service life of the product, and reduce the drip and smoke during burning.
Smart Images

Figure CN119371890A_ABST
Abstract
Description
[0001] The present invention is a divisional of 202411288162X. Technical Field
[0002] The invention relates to a method for preparing a waterborne polyurethane coating, and in particular to key materials used in a graphene-type flame-retardant, light-resistant and abrasion-resistant waterborne polyurethane coating. Background Art
[0003] Polyurethane is one of the six most important synthetic materials. It has great application value in the fields of coatings, rubber, foam plastics, fibers, adhesives, synthetic leather and functional polymers. It has become the new polymer material with the most varieties, the widest uses and the fastest development.
[0004] Waterborne polyurethane (WPU) is a most widely used environmentally friendly polymer formed by the polyaddition reaction of diisocyanate and polyol. WPU has the advantages of high mechanical strength, good flexibility, solvent resistance, corrosion resistance, etc. Therefore, WPU is widely used in the textile industry, wood processing, leather finishing, automotive industry and other fields. However, during the use of waterborne polyurethane, it is exposed to ultraviolet rays in sunlight for a long time, the surface of the film turns yellow, and the appearance change affects the service life of the product; at the same time, the polyurethane limiting oxygen index (LOI) is only 20.1%, the combustion speed is fast, and it is easy to produce droplets after combustion, causing secondary hazards. At the same time, waterborne polyurethane is often subjected to friction, collision, bending and other effects during use as a coating material, and scratches, microcracks and other physical damages will appear on the surface, resulting in the destruction of the coating, loss of function, and shortened service life. These shortcomings seriously limit the industrial application of WPU. Therefore, it must be modified to improve its flame retardancy, light resistance and wear resistance.
[0005] Chemical modification and physical modification are generally used to improve the flame retardancy and light resistance of waterborne polyurethane. The chemical modification process is complicated but the effect is good, while the physical modification process is simple but the effect is poor.
[0006] Invention patent 2023111285422 uses a hyperbranched flame retardant in a reaction vessel as a chain extender for a polyurethane synthetic prepolymer, and uses butyl glycoside (alkyl glycoside) as a chain extender to combine a permeable anionic nonionic emulsifier into the polyurethane chain segment. Saturated sodium bisulfite and ethyl carbamate are used to synergistically treat the acetone solvent in the polyurethane, and acetone is the main source of VOC in polyurethane. In addition, tannin extract from wattle bark is also used to react with phosphorus trichloride. Since wattle bark has a large number of phenolic hydroxyl groups, it reacts with P-Cl to make the obtained wattle bark easier to carbonize in phosphorus compounds, and the carbonization amount is increased. Ethanolamine is then introduced to increase the hydroxyl content in the system and increase the carbon content of the carbonizing agent to improve the flame retardancy of the system. This invention has the characteristics of not producing droplets during combustion, and has a yellowing resistance level of 3.5, and the maximum heat release degree of the polyurethane material during combustion is relatively small. However, this invention has a low yellowing resistance level, and a large maximum heat release degree during combustion, and does not involve wear resistance research. In addition, the dispersibility of thorn bark in polyurethane is poor, and there is still room for improvement.
[0007] Invention patent 202311129132X designs and prepares hyperbranched nitrogen-phosphorus-silicon flame retardants for flame retardant treatment of polyurethane, which makes up for the flammable defects of polyurethane, the problem of releasing a large number of molten droplets and large smoke when burning, and provides a new flame retardant option for flame retardant modification of polyurethane. It also adopts a combination of disulfide bonds, coumarin derivatives (photorepair) and multiple dynamic hydrogen bonds, and uses spiropyran compounds to absorb light and release energy, so that coumarin derivatives (photorepair) and disulfide bonds can improve the room temperature self-repairing durability of polyurethane. The disadvantage is that the cost of spiropyran compounds is too high, which increases the cost of the product, and does not involve wear resistance. Its pkHHR and THR still have room for improvement, and the efficiency of the prepared coumarin derivatives still has room for improvement.
[0008] Regarding the light resistance of polyurethane, some research work has also used physical blending.
[0009] He Qiuju and others mixed nano-SiO2 with MDI aromatic isocyanate by physical blending. When 0.23% SiO2 was added, the obtained polyurethane emulsion had low transmittance to ultraviolet light. Since nano-silicon dioxide has a strong absorption capacity for ultraviolet rays and a strong reflection effect on infrared rays, and the surface coordination of nano-SiO2 is insufficient and shows strong activity, it can adsorb certain pigment particles, thereby reducing the pigment attenuation caused by ultraviolet radiation. In addition, during the film-forming process, nano-silicon dioxide can form a network structure, greatly improving the aging resistance and corrosion resistance of the coating. Adding it to the raw materials can improve the yellowing resistance of polyurethane. Since nano-titanium dioxide has a large specific surface area, it can diffusely reflect part of the ultraviolet light entering the polyurethane material, absorb most of the ultraviolet energy through electron jumping, and release it in the form of vibration heat, electron-hole coupling fluorescence, etc. However, the polyurethane solution obtained by blending has poor stability, so chemical modification is required.
[0010] Some research work on the flame retardancy of polyurethane has also used physical blending.
[0011] Lv Peng and others mixed nano-silica and water-based polyurethane emulsion and found that nano-silica sol has good compatibility with water-based polyurethane. When the amount of silica sol added is less than 20%, it will not affect the appearance of the polyurethane emulsion, and its static sedimentation rate and dynamic sedimentation rate remain unchanged or have extremely small changes. Through experiments, it was found that with the increase of nano-silica sol content, the curing time of the coating gradually increased, the hardness would first increase and then stabilize, the tensile strength of the coating would first increase and then decrease, and the elongation at break would gradually decrease. The oxygen index increased from the initial 18% to 26.5%, indicating that nano-silica sol increased the combustion level of water-based polyurethane coatings. This method has the defect of poor stability of water-based polyurethane, and no research has been conducted on polyurethane droplets and smoke.
[0012] In the process of research on the flame retardancy and light resistance of existing waterborne polyurethane coatings, it is found that the light resistance is insufficient and molten droplets and smoke are generated during the combustion process. It is still necessary to improve it to improve the light resistance and flame retardancy of polyurethane to meet the needs of social development. Summary of the invention
[0013] The technical problem to be solved by the present invention is that the miscibility of ultraviolet absorbers with polyurethane coatings is poor, the light resistance level is not high, and the flame retardancy of polyurethane is poor. A dynamic reversible process is introduced into polyurethane for the first time to solve the yellowing resistance problem of polyurethane, and hydroxypropyl propargyl ether and coumarin derivatives work together to improve the light resistance of polyurethane; organic silicon compounds are introduced into the flame retardant system to increase the density of the heated Si-C carbon layer, and the nitrogen-phosphorus-silicon flame retardant is introduced into the polyurethane chain segment to reduce the dripping and combustion smoke of polyurethane combustion.
[0014] Preparation method of graphene-type flame-retardant, light-resistant and wear-resistant water-based polyurethane coating,
[0015] (1) Prepolymerization: first vacuum dry the polyol for 18 to 24 hours; then add 20 to 25 parts of the polyol and 49 to 64 parts of the isocyanate into an insert thermometer, a glass stopper, a stirring paddle, and a nitrogen tube flask, dropwise add 0.1 to 0.3 parts of dibutyltin dilaurate, raise the temperature to 80 to 85° C., rotate at 200 to 250 r / min, and react for 1 to 2 hours; adjust the temperature to 75 to 80° C., add 10 to 12 parts of polyethylene glycol with a molecular weight of 2000 g / mol into the system, and react for 1 to 2 hours to obtain the prepolymer;
[0016] (2) One-time chain extension and introduction of disulfide bonds: 2-3 parts of 1,4-butanediol BDO and 2-3 parts of disulfide compounds are added to the prepolymer, and reacted at 70-80°C for 1-2 hours. Then, 5-6 parts of polyethylene glycol monomethyl ether (MPEG) are added to the reaction system, and reacted at 70°C for 1-2 hours. During this period, the state of the reactants is constantly observed. If the viscosity increases, acetone is added in small amounts and multiple times to reduce the viscosity. Then, 3-5 parts of ultraviolet absorber, 0.6-1.5 parts of coumarin derivatives, 0.3-1.2 parts of hydroxypropyl propargyl ether, 3-5 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid are added, and the reaction is carried out at 70-80°C for 1-1.5 hours.
[0017] (3) Secondary chain extension: adjust the rotation speed to 250-300 r / min, add 1-2 parts of ethylenediamine, stir and react at 60-70° C. for 0.5-1 h, add 100-120 parts of water, keep the stirring speed at 2000 r / min at 60-70° C., react for 0.5-1 h, and obtain a graphene-type flame-retardant, light-resistant, and wear-resistant water-based polyurethane coating;
[0018] The preparation method of nitrogen-phosphorus-silicon flame retardant is as follows: using 100 mL of tetrahydrofuran as solvent, adding 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 3.9-6.5 g of organic molybdenum compound, 0.6-1 g of graphene graft and 0.5-0.7 g of azobisisobutyronitrile into a four-necked flask, reacting at 50-60° C. for 1-2 h, then adding 0.1-0.12 mol of maleic anhydride (MA) into the four-necked flask, stirring at 40-50° C. for 4-6 h, and drying in a vacuum oven to obtain a DOPO-MA reaction system; then adding 0.12-0.12 mol of maleic anhydride (MA) into the reaction system, reacting at 40-50° C. for 4-6 h, and drying in a vacuum oven to obtain a DOPO-MA reaction system. 0.14 mol diisopropanolamine (DIPA) and 0.41-0.43 g p-toluenesulfonic acid (TsOH) are placed in a flask, 50 mL of toluene is added, the mixture is heated at 90-100°C for reaction for 3-6 h, and vacuum dried at 85°C to constant weight to obtain an intermediate flame retardant; 0.01-0.015 mol tri(1-chloro-2-propyl) phosphate is added to the intermediate flame retardant, the pH is adjusted to 7.5, the mixture is reacted at 75-85°C for 1-2 h, the pH is adjusted to 7.5, 0.01-0.015 mol methyltrichlorosilane is added, the mixture is reacted at 80-85°C for 1-2 h, and the mixture is vacuum dried to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0019] The polyol is polytetramethylene glycol and polypropylene glycol, wherein the molecular weight of polytetramethylene glycol is 1000 g / mol, and the molecular weight of polypropylene glycol is 2000 g / mol;
[0020] Isocyanate is any one of HDI and MDI;
[0021] The disulfide compound is any one of 2,2'-dithiodiethanol and 2,2-diaminodiphenyl disulfide;
[0022] The ultraviolet absorber is any one of ultraviolet absorber UV-320 and ultraviolet absorber UV-531;
[0023] The preparation method of the organic molybdenum compound is:
[0024] (1) 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 75-85° C., and the mixture was stirred at 100 rpm for 18-24 h. The acetonitrile solvent was removed in a vacuum evaporator, and 50-100 mL of ethyl acetate was added. A white solid was obtained after filtration, and the solid was washed with a small amount of ethyl acetate for 3-5 times, and vacuum dried at 60-70° C. for 24-48 h to obtain intermediate A;
[0025] (2) dissolving 0.10-0.11 mol of molybdenum acetylacetonate powder in hot ethanol, slowly adding 0.10-0.12 mol of alcohol solution of intermediate A while stirring, stirring evenly, heating to 75-85° C., reflux for 12-24 h, and removing the solvent by reduced pressure distillation to obtain a dark blue powder, namely intermediate B;
[0026] (3) 0.10 mol of intermediate B and 0.1 mol of oleic acid are dissolved in 50-60 mL of dichloromethane solution, and then 40 mL of 1-2 mol / L sodium hydroxide aqueous solution is added dropwise to the mixed solution, and the reaction is stirred for 8-12 hours. The color of the product solution changes from dark blue to green. 30 mL of dichloromethane is taken to extract the product, and then the product is washed with distilled water until no precipitation is generated in the silver nitrate solution, and the product is dried to obtain an organic molybdenum compound;
[0027] The preparation method of the graphene grafted product is as follows: taking anhydrous toluene in a flask, adding 0.24-0.53g of hydroxylated graphene, 12g of 4-vinyl cyclohexyl oxide and 0.1-0.7g of stannous octoate catalyst in sequence, at pH 7.5, ultrasonic treatment for 15-30min to make the mixture uniformly mixed, stirring and reacting at 110-120°C for 16-24h under nitrogen protection, cooling the reaction mixture to room temperature, filtering, dissolving the crude product in methanol, and then adding the solution into a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residues, filtering, washing with dichloromethane and methanol respectively, filtering, and obtaining a dry graphene grafted product under vacuum conditions;
[0028] The preparation method of the coumarin derivative is as follows:
[0029] (1) Add 2.62 g of glycine methyl ester hydrochloride to a round-bottom flask, add 15-20 mL of deionized water, use triethylamine to adjust the pH to 8.5-9.0, add 5.51 g of salicylaldehyde to the reaction flask, and react at room temperature for 12-24 hours. During the reaction, an orange suspended substance appears in the flask, and the orange solid crude product is filtered and washed to obtain the orange solid crude product, which is placed in a vacuum drying oven for drying and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0030] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250 mL three-necked flask, and 100 mL of dilute hydrochloric acid (concentrated hydrochloric acid: water volume ratio of 1:2) was added to the flask, and hydrolysis was carried out at room temperature for 30 to 60 min. The pH was adjusted to 8 to 9, and a large amount of brown suspended matter precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3, and dried to obtain a coumarin derivative.
[0031] The positive effects of the present invention are:
[0032] (1) The present invention is based on the fact that disulfide bonds are dynamic weak covalent bonds with lower thermal effect response conditions than reversible covalent bonds, and disulfide bonds are easily broken to form sulfur anions or sulfur free radicals. The energy consumption effect is achieved through the recombination process between different sulfur anions or sulfur free radicals or the reversible reaction between disulfide bonds and thiol groups. By introducing disulfide bonds into waterborne polyurethane, when the polyurethane is exposed to sunlight, the disulfide bonds are first broken to form free sulfur free radicals. Under the irradiation of sunlight, the sulfur free radicals combine with each other to form disulfide bonds again, thereby absorbing the energy of sunlight on the surface of the polyurethane film and achieving the effect of yellowing resistance, thereby preparing a polyurethane coating with yellowing resistance performance;
[0033] (2) The UV absorber UV-320 is introduced into the chain end of the polyurethane by chemical grafting. Since the UV absorber can absorb UV light energy, it is then converted into heat energy that does not pollute the environment and released. Its mechanism of action is that the intramolecular hydrogen bonds in a closed state reach an excited state when exposed to ultraviolet light, and the intramolecular hydrogen bonds are opened through proton transfer, becoming an unstable keto structure and returning to the ground state. At the same time, the light energy is converted into heat energy and released, reducing the influence of ultraviolet light on the system, thereby improving the yellowing resistance.
[0034] (3) using polyol and isocyanate to react, introducing disulfide compounds as chain extenders into the prepolymer segments of polyurethane, and adding UV-320, an ultraviolet absorber, to react. The present invention utilizes the multiple effects of disulfide bonds and light absorption of ultraviolet absorbers to improve the yellowing resistance of polyurethane;
[0035] (4) The nitrogen-phosphorus-silicon flame retardant of the present invention is based on ZL2023111285422 of the research group to which the first inventor belongs. The preparation principle of the nitrogen-phosphorus-silicon flame retardant is as follows: the phosphorus-hydrogen bond (PH) in DOPO reacts with an organic molybdenum compound and a graphene graft under the action of azobisisobutyronitrile to introduce a group that suppresses smoke, and then reacts with the carbon-carbon double bond (-C=C-) on maleic anhydride to generate an intermediate. DOPO provides a carbon source and an acid source, and maleic anhydride provides a carbon source. The anhydride group in the intermediate reacts with the NH bond and part of the hydroxyl groups in diisopropanolamine to generate a new intermediate flame retardant with hydroxyl groups. Diisopropanolamine provides a gas source. When the flame retardant is decomposed by heat, ammonia and nitrogen oxides are generated on the one hand to reduce the weight of the system, and on the other hand, the generated gas is wrapped on the surface, thereby isolating the air and reducing the contact area with the combustion-supporting gas. On the other hand, the intermediate flame retardant will decompose under heat, and will continuously produce acidic substances such as polyphosphoric acid and polymetaphosphoric acid, which will promote the carbonization of the surface and form a dense porous carbon layer on its surface to achieve a flame retardant effect; at the same time, the intermediate flame retardant with hydroxyl groups is used to react with the C-Cl bond of TCPP in a weakly alkaline environment, on the one hand, the phosphorus content in the system is increased, and the acid source required for carbonization under a heated environment is increased; on the other hand, since the C-Cl content is less than the hydroxyl content of DIPA, some hydroxyl groups still react with the Si-Cl of methyltrichlorosilane to obtain nitrogen-phosphorus-silicon flame retardant. The organic silicon compound is introduced into the flame retardant system to increase the density of the heated Si-C carbon layer, and the nitrogen-phosphorus-silicon flame retardant is introduced into the polyurethane chain segment to reduce the melting drop and combustion smoke of the polyurethane combustion;
[0036] (5) Traditional inorganic molybdenum compounds have poor compatibility with polyurethanes and will precipitate after being dispersed in a polyurethane system for less than 2 hours. 1-Bromotetradecane is selected to react with N-methyldiethanolamine to form a quaternary ammonium salt compound with a hydroxyl group. Then, molybdenum acetylacetonate is used to react with the quaternary ammonium salt compound to introduce the molybdenum compound into the system to form an organic molybdenum compound compatible with polyurethane, thereby reducing the smoke release of polyurethane combustion.
[0037] (6) The present invention uses hydroxylated graphene and 4-vinyl cyclohexyl oxide under the action of stannous octoate catalyst in an alkaline environment, and the epoxy group and the hydroxyl group on the graphene are ring-opened, and the graphene is introduced into the 4-vinyl cyclohexyl oxide molecular chain, and new hydroxyl groups are also generated. The high carbonization of hydroxylated graphene and 4-vinyl cyclohexyl oxide is utilized to make the water-based polyurethane produce a relatively high and dense carbon layer during combustion, thereby reducing the combustion process. At the same time, the 4-vinyl epoxy ring is introduced into the polyurethane molecular chain to improve the wear resistance of the polyurethane.
[0038] (7) The present invention uses glycine methyl ester hydrochloride to react with salicylaldehyde to obtain 3-(2-(hydroxybenzylidene)amino) coumarin, which is hydrolyzed with dilute hydrochloric acid to break the carbon-nitrogen double bond to form an amino group. The obtained coumarin derivative has an amino group and can react with isocyanate to introduce a coumarin functional group into the polyurethane chain segment. The present invention uses the [2+2] cycloaddition reaction between two coumarin groups at around 365nm under ultraviolet light irradiation to generate a dimer with a cyclobutane structure. The optical activity of the coumarin functional group is relatively high. Under the action of ultraviolet light of different wavelengths, it can undergo a reversible photodimerization reaction and a photodepolymerization reaction at around 254nm. Energy is consumed by continuous polymerization and depolymerization, thereby reducing the yellowing effect on the polyurethane. No catalyst needs to be added during the entire reversible process.
[0039] (8) Hydroxypropyl propargyl ether is reacted with isocyanate to introduce hydroxypropyl propargyl ether with light reflecting effect into the polyurethane chain. Glutaric acid enhances the smoothness of hydroxypropyl propargyl ether on the surface of the polyurethane film, thereby forming a smooth surface that can reflect more light and improve the light resistance of the polyurethane. The present invention uses hydroxypropyl propargyl ether, coumarin derivatives, disulfide compounds and ultraviolet absorbers to improve the light resistance of polyurethane.
[0040] Part in the present invention is equivalent to g. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Electron micrograph of the carbon layer of pure waterborne polyurethane calcined at 500°C;
[0042] Figure 2 SEM image of the carbon layer of polyurethane obtained by adding nitrogen-phosphorus-silicon flame retardant when calcined at 500℃. DETAILED DESCRIPTION
[0043] The present invention is further described below with reference to the embodiments.
[0044] The chemical materials of unspecified manufacturers involved in the embodiments of the present invention can be replaced with similar products of Shanghai MacLean Biochemical Co., Ltd.
[0045] Embodiment 1
[0046] Preparation method of graphene-type flame-retardant, light-resistant and wear-resistant water-based polyurethane coating,
[0047] (1) Prepolymerization: first vacuum-dry polytetrahydrofuran ether diol and polypropylene glycol for 18 hours; then add 20 parts of polytetrahydrofuran ether diol (molecular weight 1000 g / mol) and 49 parts of HDI into an insert thermometer, a glass stopper, a stirring paddle, and a nitrogen tube flask, then add 0.1 parts of dibutyltin dilaurate, heat to 80° C., rotate at 200 r / min, react for 1 hour, adjust the temperature to 75° C., add 10 parts of polyethylene glycol with a molecular weight of 2000 g / mol into the reaction system and react for 1 hour to obtain the prepolymer;
[0048] (2) Primary chain extension and introduction of disulfide bonds: 2 parts of 1,4-butanediol BDO and 2 parts of 2,2'-dithiodiethanol were added to the prepolymer, and the mixture was reacted at 70°C for 1 hour. Then, 5 parts of polyethylene glycol monomethyl ether (MPEG, molecular weight 516 g / mol, the same below) were added to the reaction system, and the mixture was reacted at 70°C for 1 hour. During this period, the state of the reactants was constantly observed. If the viscosity increased, acetone was added in small amounts and multiple times to reduce the viscosity. Then, 3 parts of UV-320, 0.6 parts of coumarin derivatives, 0.3 parts of hydroxypropyl propargyl ether, 3 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid were added, and the mixture was reacted at 70°C for 1 hour.
[0049] (3) Secondary chain extension: adjust the rotation speed to 250 r / min, add 1 part of ethylenediamine, stir and react at 60° C. for 0.5 h, add 100 parts of water at 60° C., stir at 2000 r / min, and react at 60° C. for 0.5 h to obtain a graphene-type flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coating;
[0050] The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: 100 mL of tetrahydrofuran is used as a solvent, 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 3.9 g of an organic molybdenum compound, 0.6 g of a graphene graft, and 0.5 g of azobisisobutyronitrile are added, reacted at 50° C. for 1 h, 0.1 mol of maleic anhydride (MA) is added to a four-necked flask, stirred and reacted at 40° C. for 4 h, and dried in a vacuum oven to obtain a DOPO-MA reaction system; and the reaction system is further added with Add 0.12 mol diisopropanolamine (DIPA) and 0.41 g p-toluenesulfonic acid (TsOH) into a flask, add 50 mL of toluene, react at 90°C for 3 h, and vacuum dry at 85°C to constant weight to obtain an intermediate flame retardant; then add 0.01 mol tri(1-chloro-2-propyl) phosphate to the intermediate flame retardant and adjust the pH to 7.5, react at 75°C for 1 h, adjust the pH to 7.5, add 0.01 mol methyltrichlorosilane, react at 80°C for 1 h, and vacuum dry to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0051] The preparation method of the organic molybdenum compound is:
[0052] (1) 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 75° C., and the mixture was stirred at 100 rpm for 18 h. The acetonitrile solvent was removed by a vacuum evaporator, and 50 mL of ethyl acetate was added. A white solid was obtained after filtration and washed three times with a small amount of ethyl acetate, and dried under vacuum at 60° C. for 24 h to obtain intermediate A;
[0053] (2) dissolving 0.10 mol of molybdenum acetylacetonate powder in hot ethanol, slowly adding 0.10 mol of ethanol solution of intermediate A while stirring, stirring evenly, heating to 75° C., reflux for 12 h, and removing the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0054] (3) 0.10 mol of intermediate B and 0.1 mol of oleic acid were dissolved in 50 mL of dichloromethane solution, and then 40 mL of 1 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution, and the reaction was stirred for 8 hours. The color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution, and the product was dried to obtain an organic molybdenum compound;
[0055] The preparation method of the graphene grafted product is as follows: 50 mL of anhydrous toluene is taken into a flask, and 0.24 g of hydroxylated graphene, 12 g of 4-vinyl cyclohexyl oxide and 0.1 g of stannous octoate catalyst are added in sequence, and the mixture is subjected to ultrasonic treatment for 15 min under a pH of 7.5 to make the mixture uniformly mixed, and the mixture is stirred and reacted at 110° C. for 16 h under nitrogen protection, and the reaction mixture is cooled to room temperature and filtered, and the crude product is dissolved in methanol, and the solution is then added to a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residues, and the mixture is filtered, and washed with dichloromethane and methanol respectively, and filtered, and the product is dried under vacuum conditions to obtain the graphene grafted product;
[0056] The preparation method of coumarin derivatives is as follows:
[0057] (1) Add 2.62 g of glycine methyl ester hydrochloride to a round-bottom flask, add 15 mL of deionized water, and use triethylamine to adjust the pH to 8.5-9.0. Add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 12 h. During the reaction, an orange suspended substance appears in the flask. Filter and wash to obtain an orange solid crude product; dry it in a vacuum oven, and recrystallize it using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0058] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250 mL three-necked flask, and 100 mL of dilute hydrochloric acid (concentrated hydrochloric acid: water mixed in a volume ratio of 1:2) was added to the flask, and hydrolysis was carried out at room temperature for 30 min. The pH was adjusted to 8-9, and a large amount of brown suspended matter precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3 to obtain a coumarin derivative.
[0059] Embodiment 2
[0060] Preparation method of graphene-type flame-retardant, light-resistant and wear-resistant water-based polyurethane coating,
[0061] (1) Prepolymerization: first vacuum-dry polytetrahydrofuran ether diol and polypropylene glycol for 24 hours; add 25 parts of polypropylene glycol (molecular weight 2000 g / mol) and 64 parts of MDI into a flask with an insertion thermometer, a glass stopper, a stirring paddle and a nitrogen tube, add 0.3 parts of dibutyltin dilaurate, heat to 85° C., rotate at 250 r / min, and react for 2 hours; adjust the temperature to 80° C., add 12 parts of polyethylene glycol with a molecular weight of 2000 g / mol into the reaction system and react for 2 hours to obtain the prepolymer;
[0062] (2) Primary chain extension and introduction of disulfide bonds: add 3 parts of 1,4-butanediol BDO and 3 parts of 2,2-diaminodiphenyl disulfide, react at 80°C for 2 hours, then add 6 parts of polyethylene glycol monomethyl ether (MPEG) to the prepolymer of step (1), react at 70°C for 2 hours, observe the state of the reactants at all times during this period, if the viscosity increases, add acetone in small amounts and multiple times in time to reduce the viscosity; then add 5 parts of UV-531, 1.5 parts of coumarin derivatives, 1.2 parts of hydroxypropyl propargyl ether, 5 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid, and react at 80°C for 1.5 hours;
[0063] (3) Secondary chain extension: adjust the rotation speed to 300 r / min, add 2 parts of ethylenediamine, stir and react at 70°C for 1 hour, add 120 parts of water at 70°C, keep the stirring speed at 2000 r / min, react for 1 hour, and obtain a graphene-type flame-retardant, light-resistant, and wear-resistant water-based polyurethane coating;
[0064] The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: 100 mL of tetrahydrofuran is used as a solvent, 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 6.5 g of an organic molybdenum compound, 1 g of a graphene graft and 0.7 g of azobisisobutyronitrile are added, reacted at 60° C. for 2 h, 0.12 mol of maleic anhydride (MA) is added to a four-necked flask, stirred and reacted at 50° C. for 6 h, and dried in a vacuum oven to obtain a DOPO-MA reaction system; 0. 14 mol diisopropanolamine (DIPA) and 0.43 g p-toluenesulfonic acid (TsOH) are placed in a flask, 50 mL of toluene is added, the mixture is heated at 100°C for 6 h, and vacuum dried at 85°C to constant weight to obtain an intermediate flame retardant; 0.015 mol tri(1-chloro-2-propyl) phosphate is added to the intermediate flame retardant, the pH is adjusted to 7.5, the mixture is reacted at 85°C for 2 h, the pH is adjusted to 7.5 again, 0.015 mol methyltrichlorosilane is added at 85°C, the mixture is reacted for 2 h, and the mixture is vacuum dried to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0065] The preparation method of the organic molybdenum compound is:
[0066] (1) 0.1 mol of 1-bromotetradecane, 0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 85° C., and the mixture was stirred at 100 rpm for 24 h. The acetonitrile solvent was removed in a vacuum evaporator, and 100 mL of ethyl acetate was added. A white solid was obtained after filtration and washed 5 times with a small amount of ethyl acetate, and dried in a vacuum at 70° C. for 48 h to obtain intermediate A;
[0067] (2) Dissolve 0.11 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.12 mol of alcohol solution of intermediate A while stirring, stir evenly, heat to 85° C., reflux for 24 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0068] (3) 0.10 mol of intermediate B and 0.1 mol of oleic acid were dissolved in 60 mL of dichloromethane solution, and then 40 mL of 2 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution, and the reaction was stirred for 12 h. The color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution, and the product was dried to obtain an organic molybdenum compound;
[0069] The preparation method of the graphene grafted product is as follows: 50 mL of anhydrous toluene is taken into a flask, 0.53 g of hydroxylated graphene, 12 g of 4-vinyl cyclohexyl oxide and 0.7 g of stannous octoate catalyst are added in sequence, the mixture is subjected to ultrasonic treatment for 30 min under a pH of 7.5 to make it uniformly mixed, the mixture is stirred and reacted at 120° C. for 24 h under nitrogen protection, the reaction mixture is cooled to room temperature, filtered, the crude product is dissolved in methanol, the solution is then added to a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residues, filtered, washed with dichloromethane and methanol respectively, filtered, and the product is dried under vacuum conditions to obtain a graphene grafted product;
[0070] The preparation method of the coumarin derivative is as follows:
[0071] (1) Add 2.62 g of glycine methyl ester hydrochloride and 20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction flask, and react at room temperature for 24 h. During the reaction, an orange suspended substance appears in the flask, and the orange solid crude product is filtered and washed to obtain the solid product, which is dried in a vacuum oven and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0072] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250 mL three-necked flask, and 100 mL of dilute hydrochloric acid (concentrated hydrochloric acid: water mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 60 min. The pH was adjusted to 8-9, and a large amount of brown suspended matter precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3 to obtain a coumarin derivative.
[0073] Embodiment 3
[0074] Preparation method of graphene-type flame-retardant, light-resistant and wear-resistant water-based polyurethane coating,
[0075] (1) Prepolymerization: first, vacuum dry polytetrahydrofuran ether diol and polypropylene glycol for 21 hours; then, add 22.5 parts of polytetrahydrofuran ether diol (molecular weight 1000 g / mol) and 56.5 parts of MDI into an insert thermometer, a glass stopper, a stirring paddle, and a nitrogen tube flask, and then add 0.2 parts of dibutyltin dilaurate, raise the temperature to 80° C., rotate at 225 r / min, and react for 1.5 hours; adjust the temperature to 80° C., add 11 parts of polyethylene glycol with a molecular weight of 2000 g / mol into the reaction system, and react for 1.5 hours to obtain the prepolymer;
[0076] (2) Primary chain extension and introduction of disulfide bonds: 2.5 parts of 1,4-butanediol BDO and 2.5 parts of 2,2'-dithiodiethanol were added to the prepolymer system and reacted at 75°C for 1.5 hours. Then, 5.5 parts of polyethylene glycol monomethyl ether (MPEG) were added to the reaction system and reacted at 70°C for 1.5 hours. During this period, the state of the reactants was constantly observed. If the viscosity increased, acetone was added in small amounts and multiple times in time to reduce the viscosity. Then, 4 parts of ultraviolet absorber UV-320, 1 part of coumarin derivative, 0.75 parts of hydroxypropyl propargyl ether, 4 parts of nitrogen-phosphorus flame retardant and 0.01 parts of glutaric acid were added and reacted at 75°C for 1 hour.
[0077] (3) Secondary chain extension: adjust the rotation speed to 275 r / min and add 1.5 parts of ethylenediamine, stir and react at 65° C. for 0.5 h, add 110 parts of water at 65° C., keep the stirring speed at 2000 r / min, and react for 1 h to obtain a graphene-type flame-retardant, light-resistant, and abrasion-resistant water-based polyurethane coating;
[0078] The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: using 100 mL of tetrahydrofuran as a solvent, adding 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 5.2 g of an organic molybdenum compound, 0.8 g of a graphene graft, and 0.6 g of azobisisobutyronitrile, reacting at 55° C. for 1.5 h, then adding 0.11 mol of maleic anhydride (MA) in a four-necked flask, stirring and reacting at 45° C. for 5 h, and drying in a vacuum oven to obtain a DOPO-MA reaction system; then adding 0.13 mol diisopropanolamine (DIPA) and 0.42 g p-toluenesulfonic acid (TsOH) were placed in a flask, 50 mL toluene was poured in, the mixture was reacted at 95 °C for 4.5 h, and vacuum dried at 85 °C to constant weight to obtain an intermediate flame retardant; 0.01 mol tri(1-chloro-2-propyl) phosphate was added to the intermediate flame retardant and the pH was adjusted to 7.5, the mixture was reacted at 80 °C for 1.5 h, the pH was adjusted to 7.5 again, 0.0125 mol methyltrichlorosilane was added at 80 °C, the mixture was reacted for 1.5 h, and the mixture was vacuum dried to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant.
[0079] The preparation method of the organic molybdenum compound is:
[0080] (1) 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 80° C., and the mixture was stirred at 100 rpm for 21 h. The acetonitrile solvent was removed by a vacuum evaporator, and 75 mL of ethyl acetate was added. A white solid was obtained after filtration and washed four times with a small amount of ethyl acetate, and dried under vacuum at 65° C. for 36 h to obtain intermediate A;
[0081] (2) Dissolve 0.10 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.11 mol of alcohol solution of intermediate A while stirring, stir evenly, heat to 80° C., reflux for 18 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0082] (3) 0.10 mol of intermediate B and 0.1 mol of oleic acid were dissolved in 55 mL of dichloromethane solution, and then 40 mL of 1.5 mol / L sodium hydroxide aqueous solution was added dropwise to the mixed solution, and the reaction was stirred for 10 hours. The color of the product solution changed from dark blue to green. 30 mL of dichloromethane was taken to extract the product, and then the product was washed with distilled water until no precipitation was generated in the silver nitrate solution, and the product was dried to obtain an organic molybdenum compound;
[0083] The preparation method of the graphene grafted material is as follows: 50 mL of anhydrous toluene is taken into a flask, 0.38 g of hydroxylated graphene, 12 g of 4-vinyl cyclohexene oxide and 0.3 g of stannous octoate catalyst are added in sequence, the pH value is 7.5, ultrasonic treatment is performed for 15 min to make the mixture uniformly mixed, stirring and reacting at 115° C. for 20 h under nitrogen protection, the reaction mixture is cooled to room temperature, filtered, the crude product is dissolved in methanol, the solution is then added to a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove tin residues, filtered, washed with dichloromethane and methanol respectively, filtered, and the product is dried under vacuum conditions. The graphene grafted material;
[0084] The preparation method of the coumarin derivative is as follows:
[0085] (1) Add 2.62 g of glycine methyl ester hydrochloride and 15 mL of deionized water to a round-bottom flask, and adjust the pH to 8.5-9.0 with triethylamine. Add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 18 h. During the reaction, an orange suspended substance appears in the flask. The orange solid crude product is filtered and washed to obtain the solid. The solid product is dried in a vacuum oven and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin.
[0086] (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250 mL three-necked flask, and 100 mL of dilute hydrochloric acid (concentrated hydrochloric acid: water mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 45 min. The pH was adjusted to 8-9, and a large amount of brown suspended matter precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3 to obtain a coumarin derivative.
[0087] Preparation of polyurethane film: Pour the prepared graphene-type flame-retardant, light-resistant and abrasion-resistant water-based polyurethane coating into a polytetrafluoroethylene mold, control the thickness to 3 mm, and conduct molten drop test, cone calorimetry, light resistance and other tests.
[0088] The following is a molten drop test:
[0089] (1) Sample preparation: The prepared PU film was placed in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 h, and then taken out and cut into samples of 110 cm × 10 cm × 3 mm. Two sets of samples were prepared, with 5 samples in each set.
[0090] (2) Parameters: Clamp about 5mm from the top so that the sample is vertically downward, place a rosin board at the bottom of the sample, and pad about 0.3g of absorbent cotton on the board, evenly placed on the board. Adjust the gas flow rate to 105±5mL / min, so that the flame height reaches 20±1mm, and set the combustion time to 10s.
[0091] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button to enter the afterburning time. When the sample is completely extinguished, press the afterburning time end button and record the afterflame time and afterburning time.
[0092] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the absorbent cotton below will cause secondary combustion, and record the observation results.
[0093] The ASTM E1354-1990 (2004 standard) was used, and the cone calorimeter 2000 of the British FTT company was used for analysis and measurement. The sample was 10cm×10cm, the thickness was 3mm, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2 、THR total heat release MJ / m 2 , pSPR smoke generation rate reaches peak value m 2 / s and maximum total smoke release (TSR) m 2 / m 2 .
[0094] The yellowing resistance is determined by measuring the color change under ultraviolet light under simulated sunlight for 48 hours, using a HZ-3017 bulb-type yellowing resistance instrument.
[0095] Reflectivity determination method: Gretag Macbeth Coloreye spectrophotometer (D65 light source, 10 degree observer, including UV) was used to measure the emission level of the resin from 360nm to 750nm, wherein the maximum emissivity was defined at 660nm during the use of the present invention.
[0096] The comparative document adopts embodiment 3 of 2023111285422.
[0097] The test sample has a thickness of 0.1 cm and the abrasion resistance is tested according to GB / T22374-2018, 50g / 100r, 50 times.
[0098] Table 1 Polyurethane film-forming properties
[0099]
[0100] From Table 1, the flame retardancy (burning droplet phenomenon), pkHHR, THR, SPR smoke generation rate and TSR of the polyurethane film are significantly improved compared with the reference document (Example 3 of 2023111285422); the light resistance, an indicator of yellowing resistance, is increased from 3.5 to 4.0, the reflectivity is increased to more than 98%, the wear quality is reduced, and the abrasion resistance is significantly improved.
[0101] Table 2 Flame retardancy changes without adding some materials (based on Example 1)
[0102]
[0103]
[0104] As shown in Table 2, the combustion without graphene grafts produced molten droplets, while the pkHHR, TSR and pSPR smoke generation rates were increased without the addition of nitrogen-phosphorus-silicon flame retardants and organic molybdenum compounds, indicating that the above substances played a significant role in flame retardancy.
[0105] Table 3 Changes in light resistance without adding some materials (based on Example 1)
[0106]
[0107] As can be seen from Table 3, the yellowing resistance of the emulsion without adding some coumarin derivatives, salicylaldehyde, hydroxypropyl propargyl ether, 2,2'-dithiodiethanol and UV-320 is reduced, which shows that the above materials have good light resistance. The wear resistance of the emulsion without adding 4-vinyl epoxy ring in Example 1 is 0.0098, and no precipitate appears in the emulsion with 2,2'-dithiodiethanol and UV-320, indicating that it does not affect the stability of the emulsion.
[0108] Using Example 1 for blank comparison, it can be found from the UV-visible spectrometer that the blank group has an absorption peak only at 230nm, while the one with disulfide added has an additional absorption peak at 400nm compared with the blank group. The one with both UV absorber and disulfide added has a lot more absorption at high wavelengths (450nm, 550nm and 650nm) compared with the blank group, indicating that the UV absorber and disulfide have segmented absorption of light. Therefore, theoretically, the polyurethane emulsion with disulfide bonds and UV absorbers has a certain yellowing resistance, and this conclusion can also be drawn in combination with the color difference data results.
[0109] Figure 1 and Figure 2 The carbon layer formed when pure polyurethane and flame-retardant water-based polyurethane with nitrogen-phosphorus-silicon flame retardant added in the chain extension stage were calcined in a muffle furnace to 500°C was tested by electron microscopy. The samples were observed under an electron microscope at 1600 times the magnification. Compared with pure water-based polyurethane, the carbon layer of water-based polyurethane with flame retardant added was dense and had a complete structure, indicating that the nitrogen-phosphorus-silicon groups in the flame retardant play a synergistic role to form a dense and firm carbon layer on the surface of the polyurethane, isolating oxygen and other gases in the external gas that promote combustion from entering the interior of the polyurethane, and can effectively achieve a flame retardant effect.
Claims
1. Key materials used in graphene-based flame-retardant, light-resistant and wear-resistant water-based polyurethane coatings, characterized by: The key materials required to improve the flame retardancy, light resistance and abrasion resistance of waterborne polyurethane coatings are mainly nitrogen-phosphorus-silicon flame retardants, disulfide compounds, ultraviolet absorbers, organic molybdenum compounds, graphene grafts and coumarin derivatives; The preparation method of the nitrogen-phosphorus-silicon flame retardant is as follows: using 100 mL of tetrahydrofuran as a solvent, adding 0.1 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 3.9-6.5 g of an organic molybdenum compound, 0.6-1 g of a graphene graft and 0.5-0.7 g of azobisisobutyronitrile, reacting at 50-60° C. for 1-2 h, then adding 0.1-0.12 mol of maleic anhydride in a four-necked flask, stirring and reacting at 40-50° C. for 4-6 h, and drying in a vacuum oven to obtain a DOPO-MA reaction system; then adding 0.12-0.14 mol of diisopropanolamine DIPA and 0.41-0.43 g of p-toluenesulfonic acid into the reaction system, adding 50 mL of toluene, reacting at 90-100° C. for 3-6 h, and drying at 85 ℃ and vacuum drying to constant weight to obtain an intermediate flame retardant; then add 0.01-0.015 mol tri(1-chloro-2-propyl) phosphate to the intermediate flame retardant and adjust the pH to 7.5, react at 75-85 ℃ for 1-2 h, then adjust the pH to 7.5, add 0.01-0.015 mol methyltrichlorosilane, react at 80-85 ℃ for 1-2 h, and vacuum dry to constant weight to obtain a nitrogen-phosphorus-silicon flame retardant; The disulfide compounds are 2,2'-dithiodiethanol and 2,2-diaminodiphenyl disulfide; The ultraviolet absorber is ultraviolet absorber UV-320 and ultraviolet absorber UV-531; The preparation method of the organic molybdenum compound is: (1) Add 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence, slowly raise the temperature to 75-85°C, stir at 100 rpm for 18-24 h, remove the acetonitrile solvent in a vacuum evaporator, add 50-100 mL of ethyl acetate, filter to obtain a white solid, wash with a small amount of ethyl acetate 3-5 times, and vacuum dry at 60-70°C for 24-48 h to obtain intermediate A; (2) Dissolve 0.10-0.11 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.10-0.12 mol of ethanol solution of intermediate A while stirring, stir evenly, heat to 75-85°C, reflux for 12-24 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B; (3) Dissolve 0.10 mol of intermediate B and 0.1 mol of oleic acid in 50-60 mL of dichloromethane solution, then add 40 mL of 1-2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution, stir and react for 8-12 hours, the color of the product solution changes from dark blue to green, take 30 mL of dichloromethane, extract the product, and then wash the product with distilled water until no precipitation is generated in the silver nitrate solution, dry the product to obtain an organic molybdenum compound; The preparation method of the graphene grafted product is as follows: 50 mL of anhydrous toluene is taken into a flask, and 0.24-0.53 g of hydroxylated graphene, 12 g of 4-vinyl cyclohexyl oxide and 0.1-0.7 g of stannous octoate as a catalyst are added in sequence, the pH value is 7.5, and ultrasonic treatment is performed for 15-30 min to make the mixture uniformly mixed, and the mixture is stirred and reacted at 110-120° C. for 16-24 h under nitrogen protection, and the reaction mixture is cooled to room temperature and filtered, and the crude product is dissolved in methanol, and the solution is then added into a methanol solution mixed with a small amount of concentrated hydrochloric acid to remove the tin residue, and filtered, and the mixture is washed with dichloromethane and methanol respectively, and filtered, and the product is subjected to vacuum conditions to obtain a dry graphene grafted product; The preparation method of coumarin derivatives is as follows: (1) Add 2.62 g of glycine methyl ester hydrochloride and 15-20 mL of deionized water to a round-bottom flask, and adjust the pH to 8.5-9.0 with triethylamine. Then add 5.51 g of salicylaldehyde to the reaction flask and react at room temperature for 12-24 h. During the reaction, an orange suspended substance appears in the flask. Filter and wash to obtain an orange solid crude product, which is placed in a vacuum drying oven for drying and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin. (2) The 3-(2-(hydroxybenzylidene)amino)coumarin prepared in the previous step was transferred into a 250 mL three-necked flask, and 100 mL of dilute hydrochloric acid (a mixture of concentrated hydrochloric acid and water in a volume ratio of 1:2) was added to the flask. The flask was hydrolyzed at room temperature for 30-60 min, and the pH was adjusted to 8-9. A large amount of brown suspended matter precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3 to obtain a coumarin derivative.
2. The key material used for the graphene-based flame-retardant, light-resistant and abrasion-resistant water-based polyurethane coating according to claim 1, wherein the preparation method of the graphene-based flame-retardant, light-resistant and abrasion-resistant water-based polyurethane coating is: (1) Prepolymerization: first vacuum dry the polyol for 18 to 24 hours, wherein the polyol is polytetramethylene glycol or polypropylene glycol; then add 20 to 25 parts of the polyol and 49 to 64 parts of isocyanate into a flask with a thermometer, a glass stopper, a stirring paddle, and a nitrogen tube, add 0.1 to 0.3 parts of dibutyltin dilaurate, raise the temperature to 80 to 85°C, rotate at 200 to 250 r / min, and react for 1 to 2 hours; adjust the temperature to 75 to 80°C, add 10 to 12 parts of polyethylene glycol with a molecular weight of 2000 g / mol into the system, and react for 1 to 2 hours to obtain a prepolymer; (2) Primary chain extension and introduction of disulfide bonds: Add 2-3 parts of 1,4-butanediol BDO and 2-3 parts of disulfide compounds to the prepolymer, react at 70-80°C for 1-2 hours, then add 5-6 parts of polyethylene glycol monomethyl ether, react at 70°C for 1-2 hours, and observe the state of the reactants at all times during this period. If the viscosity increases, add acetone in small amounts and multiple times in time to reduce the viscosity; then add 3-5 parts of ultraviolet absorber, 0.6-1.5 parts of coumarin derivatives, 0.3-1.2 parts of hydroxypropyl propargyl ether, 3-5 parts of nitrogen-phosphorus-silicon flame retardant and 0.01 parts of glutaric acid, and react at 70-80°C for 1-1.5 hours; (3) Secondary chain extension: adjust the rotation speed to 250-300 r / min, add 1-2 parts of ethylenediamine, stir and react at 60-70°C for 0.5-1h, add 100-120 parts of water, maintain the stirring speed at 2000 r / min at 60-70°C, and react for 0.5-1h to obtain a graphene-type flame-retardant, light-resistant and abrasion-resistant water-based polyurethane coating.
3. The key material method used for the graphene-based flame-retardant, light-resistant and abrasion-resistant water-based polyurethane coating according to claim 2, characterized in that: The molecular weight of polytetramethylene glycol is 1000 g / mol, and the molecular weight of polypropylene glycol is 2000 g / mol.
4. The key material used for the graphene-based flame-retardant, light-resistant and abrasion-resistant water-based polyurethane coating according to claim 2, characterized in that: As the isocyanate, either HDI or MDI may be used.
Citation Information
Patent Citations
Preparation and application method of self-repairing flame-retardant molten-drop-resistant wear-resistant polyurethane coating
CN113956777A
Preparation method of matte waterborne polyurethane emulsion with flame-retardant and self-repairing functions and flame-retardant coating
CN115819704A
Preparation method of flame-retardant, light-resistant, low-VOC (volatile organic compound) and easy-to-permeate waterborne polyurethane coating
CN117551385A
Preparation method of key material for flame-retardant, light-resistant, low-VOC (volatile organic compound) and easy-to-permeate waterborne polyurethane coating
CN118389043A
Cited By
Fireproof variable frequency cable
CN121394043A
Waterborne polyurethane fiber composite material as well as preparation method and application thereof
CN121801296A